A Multi-criteria Decision Making Approach for Prioritization of the Common Market Organization Policy Measures in North Macedonia - Janeska Stamenkovska, Ivana; Dimitrievski, Dragi; Nikolov, Dimitre; Elenov, Riste (Springer International Publishing, 2021)
Introduction of market regulation policy measures should be conducted gradually in countries that are in the process of approximation towards the European Union Common Agricultural Policy. Such policies are often implemented in complex socio-economic settings, where numerous stakeholders hold different and potentially conflicting values. Therefore, an effective implementation of Common Market Organization (CMO) policies in aspiring countries requires prioritization of the different available policy instruments. The aim of this study is to determine the farmers’ preferences in context of introduction of key CMO policy measures in North Macedonia. This paper presents an Analytical Hierarchy Process based modelling framework, as a multi-criteria decision making technique, for prioritization of the CMO interventions for fresh fruits and vegetables. The results suggest that four policy measures are prioritized, among which the measures supporting the establishment of producers’ organizations and for products withdrawal are most prominent (45% of vegetable producers and 57% of fruit growers). Another priority is further given to the policy instruments supporting the introduction and the implementation of the marketing standards for fresh fruits and vegetables, followed by the introduction of the schools’ schemes. Analyses of this kind, considering the bottom-up approach in valuing the farmers’ opinions and needs for introduction of certain policy measures are scarce in practice, but are very important in tailoring the agricultural policy to the real needs of its beneficiaries. Therefore, the presented methodology might be beneficial for introduction and implementation of other policy instruments, but also in other countries aspiring to become a part of the European Union.
Keywords: Analytical Hierarchy Process, CMO Policy, Farmers’ Preferences